2023
DOI: 10.1177/10298649231157404
|View full text |Cite
|
Sign up to set email alerts
|

Passion, music, and psychological well-being

Abstract: Passionate music engagement is a defining feature of music fans worldwide. Although benefits to psychosocial well-being are often experienced by fans of music, some fans experience maladaptive outcomes from their music engagement. The Dualistic Model of Passion proposes that two types of passion—harmonious and obsessive—are associated with positive and negative outcomes of passionate engagement, respectively. This model has been employed in research on passion for a wide range of pursuits including music perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Previous Polish studies have shown that HP was associated with higher levels of subjective vitality, whereas OP was not related to subjective vitality [8,9]. Vallerand [10] highlighted that HP contributed to positive emotions and well-being, as well as preventing negative emotions, whereas OP appeared not to contribute these to these positive effects, in addition to being a risk factor for ill-being (e.g., Powell et al [11,12]).…”
Section: Links Between Passion and Healthmentioning
confidence: 94%
“…Previous Polish studies have shown that HP was associated with higher levels of subjective vitality, whereas OP was not related to subjective vitality [8,9]. Vallerand [10] highlighted that HP contributed to positive emotions and well-being, as well as preventing negative emotions, whereas OP appeared not to contribute these to these positive effects, in addition to being a risk factor for ill-being (e.g., Powell et al [11,12]).…”
Section: Links Between Passion and Healthmentioning
confidence: 94%
“…These feelings of inspiration can be akin to spiritual experiences, where individuals draw strength and meaning from music. In this way, music serves as a source of spiritual nourishment, providing individuals with a sense of purpose and connection to the world (Powell et al, 2023).…”
Section: Spiritual Benefits Of Musicmentioning
confidence: 99%
“…Music served as a powerful emotional outlet, helping individuals navigate the complex terrain of postpandemic emotions. Participants used music to soothe nerves, find solace, and express their feelings when words fell short (Powell et al, 2023).…”
Section: E Emotional Benefits Of Musicmentioning
confidence: 99%